Natural biodegradable polymeric bioadsorbents for efficient cationic dye encapsulation from wastewater - Hasan, M.; Shenashen, M.A.; Hasan, N.; Znad, Hussein; Salman, S.; Awual, Rabiul (Elsevier, 2021)
With increasing the dye contamination scenes reported around the globe, the highly promising materials are needed to clean up the water to safeguard the human health. In this work, we have investigated the naturally available carbohydrate polymeric biodegradable adsorbent of wheat flour (WF) for the encapsulation of cationic Rhodamine B (RB) dye with high sensitivity and selectivity. The adsorbent was characterized to define the functional groups existing for complexation ability to the RB dye molecules. Adsorption studies were evaluated in batch mode with the function of solution acidity, contact time, initial RB concentration, competing ions existing and reusability with using eluent. The solution acidity was exhibited the key role, and the suitable pH 5.50 was selected based on the high adsorption efficiency and sensitivity nature. Moreover, the adsorption data were highly adjacent with the Langmuir adsorption isotherms model with monolayer coverage. The determined maximum adsorption was 142.26 mg/g, which was comparable with the other forms of adsorbents in the cationic dye adsorption operations. The competing ions were not adversely affected in the RB dye adsorption by the WF adsorbent due to the complexation ability. The WF adsorbent was exhibited the high reusability based on the elution and reuses performances. The adsorbed RB dye elution was evaluated using ethanol and then the WF adsorbent was ready to use for RB dye adsorption after washing with water without significant loss in its functionality. Therefore, the biodegradable natural carbohydrate polymeric WF adsorbent will attract the scientific community as suitable bio-adsorbent for efficient cationic dye removal from contaminated water as well as the production of value-added adsorbent for water treatments for safeguarding the public health.